ISLAMIC PHILOSOPHY FROM ITS ORIGIN TO THE PRESENT - Dhita Ayu Astrellita; Yusuf Hanafi (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
Islamic Philosophy from Its Origin to the Present by Seyyed Hossein Nasr offers an in-depth analysis of the history of Islamic philosophy and its relevance in the modern era. Nasr highlights the relationship between philosophy and the spiritual dimension of Islam, explaining how this tradition, from classical to contemporary times, remains closely connected to revelation and mysticism. The book discusses the contributions of key figures such as Mulla Sadra and Ibn Sina, while also comparing the influence of Islamic philosophy on Western thought, particularly during the Middle Ages and the Renaissance. Nasr further elaborates on how Islamic philosophy remains relevant in addressing the challenges of modernity, including secularism and Western rationalism. By blending historical and philosophical concepts, this book provides valuable insights into the role of Islamic philosophy as an intellectual system rich in spiritual dimensions, offering both intellectual and spiritual solutions in an increasingly rational world.